Associations between length of music training and reading skills in children - Corrigall, Kathleen; Trainor, Laurel J. (My University, 2011)
Previous research has found that music training in childhood is associated with word decoding, a fundamental reading skill related to the ability to pronounce individual words. These findings have typically been explained by a near transfer mechanism because music lessons train auditory abilities associated with those needed for decoding words. Nevertheless, few studies have examined whether music training is associated with higher-level reading abilities such as reading comprehension, which would suggest far transfer. We tested whether the length of time children took music lessons was associated with word decoding and reading comprehension skills in 6- to 9-year-old normal-achieving readers. Our results revealed that length of music training was not associated with word decoding skills; however, length of music training predicted reading comprehension performance even after controlling for age, socioeconomic status, auditory perception, fullscale IQ, the number of hours that children spent reading per week, and word decoding skills. We suggest that if near transfer occurs, it is likely strongest in beginning readers or those experiencing reading difficulty. The strong association in our data—between length of music training and reading comprehension—is consistent with mechanisms involving far transfer.
Keywords: music training; word decoding; reading comprehension; near transfer; far transfer